Inhibitors of DNA Methylation and Histone Deacetylation as Epigenetically Active Drugs for Anticancer Therapy - Myasoedova, Veronika A.; Sukhorukov, Vasily; Grechko, Andrey V.; Zhang, Dongwei; Romanenko, Elena; Orekhov, Vawain; Orekhov, Alexander N. (Current Pharmaceutical Design, 2019)
Gene expression is regulated and tightly controlled by epigenetic mechanisms. Alterations of these mechanisms are frequently observed in various diseases, particularly, in various types of cancer. Malignant transformation is caused by the impairment of the mechanisms of cell differentiation and cell cycle control associated with epigenetic changes. Altered patterns of epigenetic modification associated with malignancies can potentially be reversed by some agents that act on the key proteins responsible for DNA/histone modification and chromatin remodelling. Examples of such substances include the inhibitors of DNA methyltransferases or histone deacetylase. During the recent years, a number of such substances have been evaluated as potential therapeutic agents against certain types of cancer in preclinical and clinical studies, and some of them have been approved for treatment of hematological cancers. Application of epidrugs for therapy of solid tumors remains, however, more challenging. In this review, we summarize the current knowledge on the most studied mechanisms of epigenetic modification and the available epigenetically active drugs.
Keywords: HDAC inhibitors